A new genus of the tribe Parahiraciini from China, with notes on the tribe (Hemiptera: Fulgoroidea: Issidae) - Che, Yanli; Zhang, Yalin; Wang, Yinglun (Zootaxa, 2013)
The new issid taxon, Folifemurum duplicatum gen. et sp. nov. from China is described and illustrated. This description includes external morphology of the adult, and structures of the male and female genitalia. The genus is placed in the tribe Parahiraciini. A diagnosis of Folifemurum gen.nov. is given and is compared to the related genus Neodurium Fennah. In addition, a key to all genera of the tribe is provided.